Предмет: Алгебра,
автор: Песнал
Очень нуждаюсь в Вашей помощи. Алгебра, 7 класс
Приложения:
Ответы
Автор ответа:
0
Как скажешь.
(2а^2+3а)^2 - а^2(1+2а)(2а-1)-3а^2(4а+1)=4а^4+12а^3+9а^2-4а^4+а^2-12а^3-3а^2=7а^2
(2а^2+3а)^2 - а^2(1+2а)(2а-1)-3а^2(4а+1)=4а^4+12а^3+9а^2-4а^4+а^2-12а^3-3а^2=7а^2
Автор ответа:
0
Спасибо)
Автор ответа:
0
(2а^2+3а)^2 - а^2(1+2а)(2а-1)-3а^2(4а+1)=4а^4+12а^3+9а^2-4а^4+а^2-12а^3-3а^2=7а^2 Держи
Автор ответа:
0
Класс
Похожие вопросы
Предмет: Геометрия,
автор: chernyshova0508
Предмет: Алгебра,
автор: idrisovamila06
Предмет: Математика,
автор: garynyhalekseev
Предмет: Литература,
автор: afsf